Oil, you’re kidding me! - Austin, James; Nadarajah, Channa Vasanth (GMS Ophthalmology Cases, 2019)
A 47-year-old female collapses with loss of consciousness secondary to septic shock and is found to have a left orbital fracture and a right orbital mass that was not seen on imaging two years ago. The mass is reported as a possible ocular melanoma. She is free of any eye pain, ophthalmoplegia or deterioration of vision but has pre-existing extensive diabetic proliferative retinopathy. One year ago, she underwent delamination and segmentation with silicone oil injected as a tamponade agent into the right eye. She is seen promptly in the ophthalmological clinic where fundoscopy reveals this mass to be the silicone oil and no further action is required.